Hippo/YAP signaling pathway in colorectal cancer: regulatory mechanisms and potential drug exploration - Zhang, Lingqiu; Zhang, Fan; Liang, Haimei; Qin, Xiangling; Mo, Yuemi; Chen, Shiyi; Xie, Jinling; Hou, Xiaotao; Deng, Jiagang; Hao, Erwei; Du, Zhengcai (Frontiers in Oncology, 2025)
ObjectiveColorectal cancer (CRC) remains a leading cause of cancer-related morbidity and mortality worldwide. The Hippo signaling pathway, particularly its downstream effector Yes-associated protein (YAP), has been identified as a pivotal regulator of CRC tumorigenesis, metastasis, drug resistance, and tumor microenvironment remodeling. This review aims to comprehensively synthesize recent advances in the regulatory mechanisms of the Hippo/YAP pathway and critically evaluate its therapeutic implications, including emerging clinical interventions and epigenetic modulation.MethodsA systematic literature review was conducted to synthesize mechanistic studies, translational research, and clinical trials involving the Hippo/YAP pathway in CRC. We focused on elucidating its upstream and downstream interactions, crosstalk with other signaling cascades, and the dual oncogenic/tumor-suppressive roles of YAP/TAZ. Epigenetic regulatory mechanisms (e.g., DNA methylation, histone modifications) and non-coding RNA-mediated regulation were rigorously analyzed. Additionally, therapeutic strategies targeting the Hippo pathway—including clinical agents, molecular inhibitors, non-coding RNAs (ncRNAs), and natural products—were systematically evaluated to assess their clinical potential.ResultsHippo pathway dysregulation drives CRC progression through aberrant YAP activation, which promotes tumor proliferation, metastasis, metabolic reprogramming, and immune evasion. Notably, emerging evidence reveals context-dependent tumor-suppressive functions of YAP/TAZ in specific CRC subtypes, such as via suppression of Wnt signaling. Epigenetic mechanisms, including DNA methylation and histone modifications, further fine-tune YAP activity. Preclinical and clinical investigations highlight the efficacy of diverse Hippo/YAP-targeted interventions, with recent clinical trials (e.g., VT3989, IK-930, IAG933, ION537) underscoring the translational promise of this pathway.ConclusionsThe Hippo/YAP axis serves as a central hub in CRC biology, exhibiting context-dependent dual roles in both oncogenesis and tumor suppression. Integrating cutting-edge insights into its regulatory networks and clinical targeting offers novel perspectives for precision oncology. By bridging fundamental discoveries with translational applications, this review establishes Hippo/YAP as a compelling therapeutic target and provides a theoretical foundation for developing innovative CRC therapies.